STRATEGI ADAPTASI MAHASISWA IISMA DALAM MENGHADAPI SYOK BUDAYA DAN KENDALA BAHASA - Noviastanti, Kartika (Puslitabmas Batam Tourism Polytecnic, 2025)
The Indonesian International Student Mobility Awards (IISMA) program provides Indonesian students with the opportunity to study abroad in various countries, including Thailand. However, students often face significant challenges related to culture shock and language barriers during their adaptation process. This study explores the strategies adopted by IISMA students at Prince of Songkla University Phuket to address these challenges and highlights the positive outcomes of successful adaptation. Data were collected through students firsthand experiences and participation in support programs such as the Thai Language and Culture Orientation Class and the Thai Buddies initiative. The findings reveal that effective adaptation was achieved through active involvement in cultural and social activities facilitated by local students. These efforts not only helped students overcome cultural differences and language barriers but also fostered cross-cultural communication skills, independence, and confidence. Additionally, the students served as cultural ambassadors, promoting Indonesian traditions to the international community. This research underscores the critical role of institutional and local support in accelerating the adaptation process for international students. By emphasizing the importance of mental readiness, intercultural competence, and flexibility, this study provides a comprehensive understanding of the challenges and strategies involved in international student mobility. The results contribute to the development of similar programs and highlight the transformative impact of cross-cultural experiences on personal and academic growth.